Colloidal Stability of Magnetite Nanoparticles Coated by Oleic Acid and 3-(N,N-Dimethylmyristylammonio)propanesulfonate in Solvents - Li, Liu; Li, Decai; Zhang, Zhili (Frontiers in Materials, 2022)
In order to understand the factors affecting the colloidal stability in the carrier liquids of different ferrofluids, magnetite nanoparticles coated by surfactants 3-(N,N-Dimethylmyristylammonio)propanesulfonate (DP) and oleic acid (OA) were fabricated as dispersions in diverse colloidal systems. The OA-coated magnetite could only be dispersed in the apolar carrier liquid (Er<5), while DP-coated magnetite particles could establish a stable colloidal system in the polar base liquid (Er>5) such as water and ethanol. The colloidal stability of OA-coated particles in the apolar solvents was mainly attributed to the steric repulsion of its outer thick liquid shell (~3 nm). Due to the absence of steric repulsion on the solid thin shell (~1 nm) on DP-coated magnetite, DP-coated particles could not be dispersed in the apolar liquid. In the polar liquid based ferrofluids, DP-coated magnetite could form an electric double layer (EDL). The total Gibbs interfacial energy was analyzed based on VOCG and DLVO theory to describe the behaviors of coated particles in solvents. In case of neutral (pH = 7) water-based colloidal, DP-coated magnetite could establish an energy barrier of ~2.2 kBT to prevent the particles from precipitation. Bare magnetite particles could form a relatively fragile colloid in water system with an energy repulsion of ~1.2 kBT. In contrast, OA-coated magnetite exhibited a severe phase separation in water-based colloidal system due to its net attraction ~ -1.3 kBT.